The Interplay of Nature and Self-Destruction in Sylvia Plath’s Poetic Vision - Suman, Shambhunath (Journal of Advanced Research in English & Education, 2025)
This article critically examines the intricate interplay between nature and self-destruction in the poetry of Sylvia Plath. It argues that Plath’s poetic vision subverts the traditional romantic notion of nature as a source of solace and harmony, instead presenting it as a hostile, volatile, and often malevolent force that mirrors the speaker's internal turmoil. The abstract highlights how natural imagery is not merely a backdrop but an active participant in the speaker's psychological and physical decline. Specific natural elements, such as fire, water, and hostile landscapes, become powerful metaphors for a consuming fever, a desire for dissolution, or a crushing sense of psychological oppression. This analysis demonstrates that the act of self-destruction in Plath’s work is often presented as a paradoxical attempt to achieve a form of radical fusion with the elemental forces of the world, a return to a primal, undifferentiated state of being. The article will explore how this dynamic is expressed through key poems, revealing that the external world of nature and the internal world of the self are locked in a symbiotic, often violent, relationship, where the impulse for annihilation is both reflected by and seeks to merge with the raw, uncompromising brutality of the natural world.